2016
DOI: 10.1002/marc.201500647
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Gene Carriers Bearing Pendant β-Cyclodextrin: The Relevance of Glycoside Permethylation on the “In Vitro” Cell Response

Abstract: The incorporation of cyclodextrins (CDs) to nonviral cationic polymer vectors is very attractive due to recent studies that report a clear improvement of their cytocompatibility and transfection efficiency. However, a systematic study on the influence of the CD derivatization is still lacking. In this work, the relevance of β‐CD permethylation has been addressed by preparing and evaluating two series of copolymers of the cationic N‐ethyl pyrrolidine methacrylamide (EPA) and styrenic units bearing pendant hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 55 publications
2
8
2
Order By: Relevance
“…Contrarily, the permethylated systems tended to form smaller particles with increasing content of the permethylated neutral unit. This behavior is in agreement with the reported differences obtained in our previous work, with hydroxylated and permethylated CD-derivatives, where the hydroxylated moieties form bigger particles, probably due to hydrogen bonding between the hydroxyl groups of the glucose units and the amino N or O or the carboxyl and phosphate groups of DNA, respectively [32].…”
Section: Polyplex Formation and Characterizationsupporting
confidence: 91%
“…Contrarily, the permethylated systems tended to form smaller particles with increasing content of the permethylated neutral unit. This behavior is in agreement with the reported differences obtained in our previous work, with hydroxylated and permethylated CD-derivatives, where the hydroxylated moieties form bigger particles, probably due to hydrogen bonding between the hydroxyl groups of the glucose units and the amino N or O or the carboxyl and phosphate groups of DNA, respectively [32].…”
Section: Polyplex Formation and Characterizationsupporting
confidence: 91%
“…Poly(N-ethyl pyrrolidine methacrylamide) (EPA) is a cationic, linear, non-toxic, and non-crosslinked polymer that was synthesized and characterized for the first time by Velasco and colleagues in 2007 [ 15 ]. The synthesis and characterization of other polymer systems, except terpolymers, ECDP, composed of EPA-HCD-APEG, have been previously described [ 17 , 19 , 22 ]. EG is a copolymer of EPA with the monomer, GLSt, which is derived from glucose, with 0.9/0.1 (EG10) and 0.95/0.05 (EG5) molar fractions, whereas EM is a copolymer of EPA and MGLSt, a permethylated glucose monomer, with 0.9/0.1 (EM10) and 0.95/0.05 (EM5) molar fractions [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…HPMA is a precursor with a biocompatible nature, whose copolymerization of HPMA with cationic precursors enhances the performance as gene carriers of cationic component homopolymers and allows the modulation of the charge density of polymeric entities and their interaction with the surrounding media in a flexible and tailored way [ 18 ]. ECD is a copolymer of EPA and a cyclodextrin (HCD)-derivative monomer designed to improve the cellular uptake of polyplexes, and good interactions with the cellular membrane have been described before, and their transfection capability improves when fibroblasts cell lines are used [ 22 ]. Due to their unique structure with multiple hydroxyl groups, amphiphilic cyclodextrin-based polymers provide low toxicity, good bioavailability, and biodegradability, as well as the ability to form well-defined aggregated nanostructures [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported higher effectiveness through polymer modification, which consisted of the introduction of secondary and tertiary amines to enhance its buffering capacity [28], thus improving its properties when releasing the genetic material into the cytoplasm. Furthermore, more complex entities such as cyclodextrins have been anchored to different polymers to increase the complexing capacity of the genetic material [29][30][31].…”
Section: Introductionmentioning
confidence: 99%